An Analysis on the Fulfilment of Justice Principles for Victims of Fatal Vigilantism - Adriela, Jessica Zelma; Firmansyah, Hery (Universitas Islam Negeri Alauddin Makassar, 2026)
The phenomenon of vigilantism represents a violation of the law that arises due to the low level of public trust in the effectiveness of formal law enforcement in Indonesia. In the context of criminal law, such actions not only eliminate the role of law enforcement officers as justice enforcers but also deprive victims of their rights to legal protection, justice, and legal certainty that should be guaranteed by the state. Acts of vigilantism also reflect a crisis of legitimacy in law enforcement institutions, a weak legal culture in society, and the state’s limited presence in providing security for its citizens. This study aims to analyze the fulfillment of the principle of justice for victims of vigilantism that resulted in death by applying the theory of justice and the theory of punishment purposes as the conceptual framework. The research method used is a qualitative approach through literature study involving statutory regulations, legal literature, and relevant court decisions. The results indicate that the implementation of justice for victims remains suboptimal since the legal system is still offender-oriented, while the protection, recovery, and respect for victims’ rights are often neglected. Sentences imposed are relatively light and disproportionate to the fatal consequences caused, namely the loss of life. Therefore, a reformulation of sentencing policies, strengthened victim protection mechanisms, and transparent, firm, and fair law enforcement are needed to restore public trust in the justice system sustainably. This study contributes to the study of justice, especially in the proceedings of criminal law.